1992
DOI: 10.1177/074823379200800505
|View full text |Cite
|
Sign up to set email alerts
|

Does Nitrogen Dioxide Exposure Increase Airways Responsiveness?

Abstract: A number of reports have suggested that exposure to nitrogen dioxide (NO2) may cause increased airways responsiveness (AR). Twenty studies of asthmatics and five studies of healthy subjects exposed to NO2 were used to test this hypothesis using a simple method of meta-analysis. Individual data were obtained for the above studies and the direction of change in AR was determined for each subject. Only studies with available individual data were used. Subjects from these studies whose directional change in AR cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
1
4

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 26 publications
0
46
1
4
Order By: Relevance
“…[14][15][16] However, other studies have shown no respiratory effects on asthmatics following exposures to even higher levels. 17,18 Controlled exposures of healthy (non-asthmatic) subjects to NO 2 concentrations above 1,000 ppb for 1 hour or longer indicate increased airway responsiveness; 16,19,20 exposures to lower NO 2 levels have not produced any effects.…”
Section: Introductionmentioning
confidence: 95%
“…[14][15][16] However, other studies have shown no respiratory effects on asthmatics following exposures to even higher levels. 17,18 Controlled exposures of healthy (non-asthmatic) subjects to NO 2 concentrations above 1,000 ppb for 1 hour or longer indicate increased airway responsiveness; 16,19,20 exposures to lower NO 2 levels have not produced any effects.…”
Section: Introductionmentioning
confidence: 95%
“…NO 2 induces an airway inflammation, probably restricted to the smaller airways and the terminal bronchioles, at least after a single exposure [15]. The main effect of NO 2 in human exposure studies has been on bronchial responsiveness, usually seen at concentrations of o1,800 mg?m -3 in healthy subjects and ,200-500 mg?m -3 in patients with asthma [16] or chronic obstructive pulmonary disease (COPD) [17]. NO 2 also has an amplifying effect on the asthmatic response to allergen exposure.…”
mentioning
confidence: 99%
“…Par contre , une méta -ana lyse de 25 études contrôlées [5] suggère que l'hyperréactivité bronchique chez les sujets sains augmente rait après exposition à des co ncent~a tio ns de N0 2 supérieures à 1 000 ppb . Enfin , c he z les ast hm at iqu es l'hype rréact ivité bronchique serait majorée, même pour des concentrations inférieures à 1 000 ppb de N0 2· L'effet de l'inhalation de N0 2 à la concentratio n de 400 ppb a été étudié lors de tests de provocation aux acariens, chez un nombre réduit de patients ; une légère acce ntuation du bronchospasme induit par la dose limi nair e d'allergène était obse rvée après inhalation préa lable de N0 2 (41 % de chu te du VEMS ), et cett e chute éta it majo rée après une exposition combiné e de N0 2 et de S02 (60 % de chute du VEMS) [6].…”
Section: Les Polluants Chimiques Domestiquesunclassified